ICARDA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The International Center for Agricultural Research in the Dry Areas (ICARDA) was established in 1977 as one of 13 centres supported by CGIAR (the ConsuItative Group on International Agricultural research), which is a consortium of donor governments...